Pengembangan Kepribadian Konselor Melalui Kegiatan Kepramukaan di UKK Racana IAIN Surakarta - Nurika Indah Sofantiyana (Academica : Journal of Multidisciplinary Studies, 2017)
This research is intended to explore various of Scout activities in Racana of IAIN Surakarta that contribute and have a role in developing the personality of the counselor. Using a descriptive qualitative approach, the data are collected through interviews then analyzed with literature review. The results show that activities in Racana such as Riska, Pandega, Binsat, Kerekaan and daily activities are not only aimed at forming professionalism in the field of scout profession but also have a role in developing counselor personality. Personality developed such as empathy, responsibility, confident, socially sensitive, sociable, self-understanding, understanding each other, and also professionalism. Activities at Racana are also useful for self-actualization for counselors. Thus, Racana activities can be maximized to develop counselor's personality.Keywords: Personality, Counselor, Scout